2010
DOI: 10.1248/bpb.33.1484
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester Inhibits Differentiation to Adipocytes in 3T3-L1 Mouse Fibroblasts

Abstract: We investigated the inhibitory effect of caffeic acid phenethyl ester (CAPE) on the differentiation of 3T3-L1 mouse fibroblasts to adipocytes. 3T3-L1 cells were differentiated for adipocytes given high glucose Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 1 mM dexamethasone (DEX), 500 mM isobutylmethylxanthine (IBMX), and 5 mg/ml insulin for 7 days. After differentiation, cells were stained with Oil-Red-O to detect oil droplets in adipocytes. Additionally, the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…It was suggested that inhibition of lipid accumulation was caused by CAPE treatment in 3T3-L1 differentiation of adipocytes through the inhibition of PPARgamma, C/EBPalpha and late adipogenic markers, such as Fas and aP2 expression. 8) IRS-1 plays an essential role in adipocytes differentiation and adipogenensis. 18) In the present study, we confirmed that increased IRS-1 was significantly reduced by CAPE treatment, implying that CAPE blocked adipocytes differentiation in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that inhibition of lipid accumulation was caused by CAPE treatment in 3T3-L1 differentiation of adipocytes through the inhibition of PPARgamma, C/EBPalpha and late adipogenic markers, such as Fas and aP2 expression. 8) IRS-1 plays an essential role in adipocytes differentiation and adipogenensis. 18) In the present study, we confirmed that increased IRS-1 was significantly reduced by CAPE treatment, implying that CAPE blocked adipocytes differentiation in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAPE ( Figure 1) is known to have antimitogenic, anticarcinogenic, antiinflammatory, and immunomodulatory properties [12,13]. We previously documented that CAPE suppressed the differentiation of 3T3-L1 to adipocytes [14]. It has also been suggested that ROS production increased during the differentiation of 3T3-L1 to adipocytes [15].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that CAPE has suppression effect on 3T3-L1 differentiation to adipocytes and production of adipocytokines during adipogenesis. 20,21) In the present study, we investigated the inhibitory effect of CAPE on LPS-induced production of pro-inflammatory cytokines in a macrophage cell line, RAW264.7, and the suppressive effect of CAPE on 3T3-L1 hypertrophic adipocytes, which are stimulated by pro-inflammatory cytokines present in the supernatant from RAW264.7 macrophages. 4 cells/100 µL/well.…”
mentioning
confidence: 99%